ASSETS TURNOVER, CASH POSITION, LEVERAGE, DAN PERTUMBUHAN PERUSAHAAN SEBAGAI DETERMINAN TERHADAP KEBIJAKAN DIVIDEN - Julianty Violetta Sari S; Nur Cahyonowati (Diponegoro Journal of Accounting, 2015)
This study aims to analyze and provide empirical evidence about the effect of assets turnover, cash position, leverage, and company’s growth on dividend policy. Several previous studies showed varying results. To obtain valid results, then doing a test on each variable based on the hypothesis constructed. The samples used were selected by purposive sampling method. The population was 125  manufacturing  companies  listed  in  Indonesia  Stock  Exchange.  After  reduced  with  some criteria, 27 companies identified as samples. Observation period was 2010 to 2012, so the total number of sample used was 81 samples. Multiple regressions were used to examine the hypothesis. The results indicate that assets turnover and leverage are significantly affect the dividend policy. On the other side, cash position and company’s growth have no effect on the dividend policy.